In perfect time : a novel - Sundin, Sarah (Sundin, Sarah. Wings of the nightingale, 2014)
Bold, sophisticated, and coy, Army Air Force flight nurse Lt. Kay Jobson collects hearts whever she flies, leaving men pining in airfields all across Europe. So how can ruggedly handsome C-47 pilot Lt. Roger Cooper be all but immune to her considerable charms? In fact, he seems to do everything he can to avoid her. Still, as they cross the skies between Italy and southern France, evacuating the wounded and delivering paratroopers and supplies, every beat of their hearts draws them closer. Can they overcome the fears and misunderstandings of the past in order to take hold of the future?